The Role of Gamification and Social Media Marketing on Brand Loyalty through Customer Engagement: A Case Study of Duolingo - Sabrina, Shellyana Kholifatul; Wibawa, Berto Mulia (Transpublika Publisher, 2026)
Gamification and social media marketing strategies has become a significant trend in digital marketing, including in language learning platforms such as Duolingo. Gamification elements, such as streaks, leaderboards, and daily challenges, are integrated to enhance user motivation, while social media marketing through creative approaches on TikTok is employed to boost customer engagement. However, despite the success of these approaches in driving interactions, their effectiveness in fostering long-term brand loyalty requires further in-depth evaluation. This research aims to explore the impact of gamification and social media marketing on brand loyalty through customer engagement. Utilizing the Self-Determination Theory (SDT) framework, this research examines the relationships between variables using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method and sentiment analysis based on user data from X. Online surveys and text mining techniques are applied to collect quantitative and qualitative data, ensuring that the research outcomes reflect user perspectives holistically. The study confirms that Duolingo's gamified features and social media presence enhance customer engagement and brand loyalty. User sentiment toward gamification is largely positive, though technical issues generate criticism. Social media content is valued for entertainment but lacks educational depth. PLS-SEM analysis aligns with Self-Determination Theory, demonstrating how Duolingo satisfies users' needs for competence, autonomy, and relatedness. Future research should incorporate multi-platform data, longitudinal methods, and variables like brand experience. These findings provide actionable guidance for businesses implementing interactive digital strategies.